The Moderating Effect of Prior Knowledge on Cue Utilization in Product Evaluations - Rao, Akshay R.; Monroe, Kent B. (Journal of Consumer Research, 1988)
This article examines the dissimilar use of product information cues in product evaluations by differentially familiar subjects. Specifically, the use of price cues and intrinsic product cues for the assessment of product quality is hypothesized to depend on prior knowledge. For a product with a positive quality-price association in the marketplace, the study shows that low-familiar and highly familiar subjects tend to perceive a stronger price-quality relationship than do moderately familiar subjects. Moreover, as subjects product familiarity increases, the use of intrinsic cues for product quality assessments tends to become relatively stronger.